(untitled) (Scientific Journal of Actuarial Finance and Accounting, 2024)
With the acceleration of globalization and information technology, China's digital economy continues to expand and become an important engine to promote national economic growth. This paper establishes a multi-dimensional index system covering digital industrialization, industrial digitalization, digital infrastructure and economic environment, and uses the entropy method to measure the comprehensive index of digital economy in each province to reveal its development process and regional differences. The results show that the eastern coastal region is significantly ahead of the central and western regions, and infrastructure and policy support are the key influencing factors. The empirical results of this paper provide data support for further optimizing regional digital economy policies.